THE INFLUENCE OF ACADEMIC CULTURE, ORGANIZATIONAL COMMUNICATION CLIMATE, QUALITY OF SERVICE AGAINST CUSTOMER SATISFACTION AT HIGH SCHOOL TRANSPORTATION MANAGEMENT - Ervin Agung Priambodo; Thamrin Abdullah; Maruf Akbar (Program Pascasarjana Universitas Negeri Jakarta, 2017)
The purpose of this research is to determine the influence of academic culture, organizational communication climate, and service quality to customer satisfaction at Trisakti High School of Management Transportation Jakarta (STMT Trisakti Jakarta). This research tries to answer the problems that can give influence to customer satisfaction. The research was conducted at Trisakti High School of Management Transportation Jakarta with a population of 1,203 people, and a sample of 177 people all of whom are STMT Trisakti students in thesixth semester. This research uses quantitative approach with path analysis method. Hypotheses in this study show: (1) academic culture has a direct positive effect on customer satisfaction, (2) organizational communication climate has a direct positive effect on customer satisfaction, (3) service quality has positive direct effect on customer satisfaction, (4) academic culture has direct effect Positive to the quality of service, (5) organizational communication climate has a direct positive effect on service quality. Therefore, to improve customer satisfaction of customer satisfaction at STMT Trisakti Jakarta, must improve academic culture, organizational communication climate, and service quality. Keywords : Academic culture, organizational communication climate, service quality, and customer satisfaction.